2020
DOI: 10.5614/ajht.2020.18.2.06
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Tourism Master Plan (TMP 2013-2020) – Perceptions of Myanmar’s Tourism Stakeholder

Abstract: This paper is a work-in-progress that aims to assess the evaluation of the 2013-2020 Myanmar Hotel and Tourism Ministry (MHT) Tourism Master Plan (TMP 2013-2020) from the perceptions of the country's tourism stakeholders. The TMP aims to improve tourism outcomes through sustainable practices such as more practical education and training of industry staff as opposed to traditional rote learning methods which was a major concern discussed during the Australia-Myanmar Institute (AMI) conferences in Yangon and Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…In several cases, researchers from foreign institutions were found, such as Nobukazu Nagakoshi (L. Hakim & Nagakoshi, 2008), David Reeve (Valeriani et al, 2020), Guillaume Tiberghien (Ristiawan & Tiberghien, 2021), and Kumiko Shishido (Sadguna et al, 2020), or where the member researchers are from different international institutions from the first researcher, such as the Hess et al, (2021) article, both of which were ignored, because the data collection only refers to the identity of the first researcher. Twenty-five international researchers were recorded from 15 countries: United States (Acharya, 2021), Australia (Ayoub, 2020;Prideaux & Tao, 2005;Zeng, 2005), Bangladesh (Bhuiyan & Ismail, 2018), Netherlands (Rindrasih, 2015), Bulgaria (Slavov & Palupi, 2019), Ethiopia (Eshete et al, 2020), Philippines (Abansi, 2012;Arreza & Esguerra, 2021;Era & Rosario, 2020;Espiritu & Guevarra, 2015;Luna, 2021), India (De, 2012;Dey, 2013;Vinodan, 2010), United Kingdom (Hess et al, 2021), Italy (Brida, 2008), South Korea (Anele & Sam-Otuonye, 2021), Egypt (Abdou et al, 2020), France (Loustaunau, 2018), Romania (Voda et al, 2019), and Thailand (Chaichompoo, 2011;Songkhla & Somboonsuke, 2012;Southiseng & Walsh, 2010). The authors noticed that the tendency of international scholars to publish their studies in national tourism journals is indicated to have increased in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In several cases, researchers from foreign institutions were found, such as Nobukazu Nagakoshi (L. Hakim & Nagakoshi, 2008), David Reeve (Valeriani et al, 2020), Guillaume Tiberghien (Ristiawan & Tiberghien, 2021), and Kumiko Shishido (Sadguna et al, 2020), or where the member researchers are from different international institutions from the first researcher, such as the Hess et al, (2021) article, both of which were ignored, because the data collection only refers to the identity of the first researcher. Twenty-five international researchers were recorded from 15 countries: United States (Acharya, 2021), Australia (Ayoub, 2020;Prideaux & Tao, 2005;Zeng, 2005), Bangladesh (Bhuiyan & Ismail, 2018), Netherlands (Rindrasih, 2015), Bulgaria (Slavov & Palupi, 2019), Ethiopia (Eshete et al, 2020), Philippines (Abansi, 2012;Arreza & Esguerra, 2021;Era & Rosario, 2020;Espiritu & Guevarra, 2015;Luna, 2021), India (De, 2012;Dey, 2013;Vinodan, 2010), United Kingdom (Hess et al, 2021), Italy (Brida, 2008), South Korea (Anele & Sam-Otuonye, 2021), Egypt (Abdou et al, 2020), France (Loustaunau, 2018), Romania (Voda et al, 2019), and Thailand (Chaichompoo, 2011;Songkhla & Somboonsuke, 2012;Southiseng & Walsh, 2010). The authors noticed that the tendency of international scholars to publish their studies in national tourism journals is indicated to have increased in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…25 peneliti internasional berasal dari 15 negara: Amerika Serikat (Acharya, 2021), Australia (Ayoub, 2020;Prideaux & Tao, 2005;Zeng, 2005), Bangladesh (Bhuiyan & Ismail, 2018), Belanda (Rindrasih, 2015), Bulgaria (Slavov & Palupi, 2019), Etiopia (Eshete et al, 2020), Filipina (Abansi, 2012;Arreza & Esguerra, 2021;Era & Rosario, 2020;Espiritu & Guevarra, 2015;Luna, 2021), India (De, 2012;Dey, 2013;Vinodan, 2010), Inggris (Hess et al, 2021), Italia (Brida, 2008), Korea Selatan (Anele & Sam-Otuonye, 2021), Mesir (Abdou et al, 2020), Prancis (Loustaunau, 2018), Rumania (Voda et al, 2019), dan Thailand (Chaichompoo, 2011;Songkhla & Somboonsuke, 2012;Southiseng & Walsh, 2010). Dari frekuensi artikel bisa dilihat bahwa kecenderungan akademisi internasional untuk mempublikasikan kajian mereka pada jurnal pariwisata nasional terindikasi meningkat pada beberapa tahun terakhir.…”
Section: Diskusiunclassified